Implementasi Model Project Based Learning dalam Pembelajaran Menulis Karya Ilmiah pada Mahasiswa - sabitul kirom (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The research objective is to describe the application of the Project Based Learning (PjBL) model which is process and product oriented in learning to write scientific papers. The research method used is descriptive qualitative. The research subjects were 2nd semester students for the 2022/2023 academic year Computer Systems Study Program, Balitar Islamic University. Sources of data include results of performance observations and scientific work products. The results showed that the PjBL model could facilitate students in achieving CPL with an average score of 81. By applying the PjBL model, students could develop ideas in writing scientific papers. The PjBL model is also able to develop aspects of cooperation, social sensitivity, ethics and morals, as well as good and correct Indonesian language skills. Based on the results of the research, it can be concluded that the PjBL model can support the achievement of learning to write scientific papers and develop aspects of cooperation, ethics, morals, and good and correct language skills.